2013
DOI: 10.4269/ajtmh.12-0552
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Polyparasitic Infections on Anemia and Undernutrition among Kenyan Children Living in a Schistosoma haematobium-Endemic Area

Abstract: Abstract. We measured prevalence of Schistosoma haematobium, Wuchereria bancrofti, Plasmodium falciparum, hookworm, and other geohelminths among school-aged children in four endemic villages in Kwale County, Kenya and explored the relationship between multiparasite burden, undernutrition, and anemia. In 2009-2010 surveys, cross-sectional data were obtained for 2,030 children 5-18 years old. Infections were most prevalent for S. haematobium (25-62%), hookworm (11-28%), and falciparum malaria (8-24%). Over one-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 39 publications
3
69
4
Order By: Relevance
“…For early life/low intensity infections, prevalence estimates based on egg detection are known to be significant underestimates of the true infection rate. 15,27 Adequately powered studies, applying sensitive antigen-detection tests for the diagnosis of Schistosoma infection, are needed to further investigate the likely association between the inflammation caused by schistosomiasis haematobia and anemia. While it is unlikely that children in this age group were HIV positive, we did not determine HIV status for study participants, however there is always a chance that some of these children were HIV infected, which could have allowed additional undetected opportunistic infections that could have contributed to AI and so obscure the results of our parasite-focused analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For early life/low intensity infections, prevalence estimates based on egg detection are known to be significant underestimates of the true infection rate. 15,27 Adequately powered studies, applying sensitive antigen-detection tests for the diagnosis of Schistosoma infection, are needed to further investigate the likely association between the inflammation caused by schistosomiasis haematobia and anemia. While it is unlikely that children in this age group were HIV positive, we did not determine HIV status for study participants, however there is always a chance that some of these children were HIV infected, which could have allowed additional undetected opportunistic infections that could have contributed to AI and so obscure the results of our parasite-focused analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies 34,42,43,45,47,49,51 assessed hookworm only, while four studies 25,27,31,50 assessed A. lumbricoides only. Three studies described STH without speciation.…”
Section: 33mentioning
confidence: 99%
“…Three studies described STH without speciation. 35,36,46 Twelve studies 8,26,28,32,33,35,41,43,46,[49][50][51] assessed the impact of co-infection on anemia, using various measurements. Five studies 26,28,32,33,49 quantitatively reported anemia with the mean Hb level in various age groups and pregnant women.…”
Section: 33mentioning
confidence: 99%
“…However, within the Americas, the Central American Republic of Guatemala has the highest rate of stunting, with a 49·8 % prevalence according to the most recent national nutrition survey (3) , when measured with respect to the WHO standards (4) . The designation of stunting as 'chronic malnutrition' would implicitly suggest a dietary origin, but a diverse series of environmental influences including microbial contamination (5) , mycotoxins (6,7) , indoor smoke (8) , recurrent diarrhoea (9,10) , helminth infection (11,12) and environmental enteric dysfunction (13,14) have been postulated to explain more of the variance than can be explained simply by poor nutrient intake (5,15) . On a global basis, UN statistics document a progressive and steep decline in length-for-age status during the first three years of life (16) .…”
mentioning
confidence: 99%